Turbidity Characteristics of The Waters on The Padelegan Beach, Pademawu District, Pamekasan Regency, East Java - Onie Wiwid Jayanthi; Ary Giri Dwi Kartika; Ashari Wicaksono; Amalia Hariyanti; Dwi Syadina Putri; Putri Ayu Rahmadani (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
Padelegan Beach is one of the beaches used for tourism and seaweed cultivation activities, which is located in Pademawu District, Pamekasan Regency. The distribution of water turbidity plays an important role in the success of seaweed cultivation activities and salt ponds along the Jumiang coast. The purpose of this research is to know the condition of turbidities distribution in Jumiang waters. The sampling method used the purposive sampling method with the location of nine sampling stations. The location of the turbidity measurement is based on thereare near the coast (points 1, 2, 3), beaches (points 4, 5, 6), and the high seas (7, 8, 9). Turbidity was measured using the Lutron TU-2016 Turbidity Meter. The results show that the turbidity distribution at station points near the coast is higher in value than at high sea station points. The highest turbidity value is 29,82 NTU in the coastal area, while the lowest is 4,35 NTU the offshore. The turbidity value in Jumiang coastal waters shows a value below the threshold for turbidity that is intended for cultivation activities.Keywords: characteristics, turbidity, The Padelegan Beach